Presenting a Model of the Effect of Cognitive Bias on Mental Health and Quality of Life in Elderly Women with the Mediating Role of Mindfulness - Yousefpour, Nahideh (KMAN Counseling & Psychology Nexus, 2026)
The present study aimed to investigate the effect of cognitive bias on mental health and quality of life in elderly women, with the mediating role of mindfulness. This research is applied in purpose, quantitative in approach, and descriptive-survey in design. The statistical population consisted of Iranian elderly women aged over 60 years. Based on G*Power software calculations and using convenience and purposive sampling methods, 129 participants were selected. Data collection instruments included the Mindfulness Questionnaire by Brown et al. (2007), the Quality of Life Questionnaire by Ware and Sherbourne (1992), the Cognitive Bias Questionnaire by Woody et al. (1997), and the General Health Questionnaire by Goldberg (1972). For data analysis, in addition to descriptive statistics, Kolmogorov–Smirnov tests, structural equation modeling, and the Sobel test were employed. All analyses were conducted using SPSS version 23 and SmartPLS version 3.1.1 at a significance level of 0.05. The results indicated that the research model demonstrated a good fit. Cognitive bias had a significant negative effect on mental health (t = 4.698, p = 0.001), quality of life (t = 5.681, p = 0.001), and mindfulness (t = 11.016, p = 0.001) among elderly women. Moreover, mindfulness had a significant positive effect on mental health (t = 2.930, p = 0.004) and quality of life (t = 6.681, p = 0.001). The findings also showed that mindfulness plays a significant mediating role in reducing the effect of cognitive bias on mental health (z = −6.019, p = 0.001) and quality of life (z = −8.527, p = 0.001). Therefore, mindfulness reduces the negative impact of cognitive bias on mental health and quality of life in elderly women.